9*(3+4)=

Simple and best practice solution for 9*(3+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9*(3+4)= equation:


Simplifying
9(3 + 4) = 0

Combine like terms: 3 + 4 = 7
9(7) = 0

Multiply 9 * 7
63 = 0

Solving
63 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 1.5x+3y-z=-8 | | x-x*0.1=86.96 | | -5(1)=8+4m | | x(5+x)=(x*x)+3x+1 | | 12q-4=32 | | 2(3x-4)+5-4x=11 | | 24x+1.8-x+3=16-1 | | 16x=.6x | | 0.8(x-5)=0.4x-20 | | -Rx+5y=-T | | 7x+-5=4x+4 | | 24x+1*8-x+3=16-1 | | f(x)=x(x+1)(x-6) | | -5(0)=8+4m | | (M+3)(m-4)= | | 56+12x=8+8x | | D=2abc | | 1.5r+15=45r | | -3X+10+4X=13 | | 2ax=10a-3ax | | 8y+8=7y-12 | | 4t-2=33-3y | | 7m+38=5m-16 | | 3y=9-4x | | 3c+17=8 | | 3x-8x-5=-15 | | 5x-17=3x+4 | | 4q+3=-9 | | p-4+-9=p | | 2x(x+3)-7=5(5-x)+7(x+1) | | -5c(4c^2-2c)= | | 8x+(x*x)(x*x)=11 |

Equations solver categories